2018
DOI: 10.1111/jog.13716
|View full text |Cite
|
Sign up to set email alerts
|

Early medical abortion with self‐administered low‐dose mifepristone in combination with misoprostol

Abstract: AimThe aim of the present study was to investigate the safety and efficacy of low‐dose mifepristone combined with self‐administered misoprostol for termination of early pregnancy.MethodsA total of 533 women seeking medical abortion in early pregnancy (≤49 days since the last menstrual period) were divided randomly into hospital‐ (H‐Mis, 250) and self‐ (S‐Mis, 283) administered misoprostol groups. Women in two groups took 100 mg of oral mifepristone in hospital followed by 200 μg of sublingual misoprostol 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Women in selected studies were satisfied both in settings where the option of in‐person abortion care was available and in settings where few alternatives existed. The mean rates of satisfaction were similar to those in studies on medical abortion provided in‐person, of which several also show a preference for self‐administration of misoprostol at home . There were only two studies evaluating acceptability of medical abortion through TM for providers, but they indicated that it is highly acceptable for providers and iis associated with greater flexibility and efficiency …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Women in selected studies were satisfied both in settings where the option of in‐person abortion care was available and in settings where few alternatives existed. The mean rates of satisfaction were similar to those in studies on medical abortion provided in‐person, of which several also show a preference for self‐administration of misoprostol at home . There were only two studies evaluating acceptability of medical abortion through TM for providers, but they indicated that it is highly acceptable for providers and iis associated with greater flexibility and efficiency …”
Section: Discussionsupporting
confidence: 58%
“…The mean rates of satisfaction were similar to those in studies on medical abortion provided in-person, of which several also show a preference for self-administration of misoprostol at home. [46][47][48] There were only two studies evaluating acceptability of medical abortion through TM for providers, but they indicated that it is highly acceptable for providers and iis associated with greater flexibility and efficiency. 40,41 Abortion through TM may at the least be a highly autonomous option and at most a life-saving alternative for women seeking abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were RCTs, and included data from 1452 women. [21][22][23] Sixteen studies were NRSs and included data from 10 124 women. 16 17 24-36 Sixteen studies were conducted in lowto-middle resource settings (Bangladesh, 25 26 India, 28 30 34 Nepal, 22 31 China, 21 23 Vietnam, 32 33 35 Tunisia, 29 35 Nigeria, 36 Albania 27 and Turkey 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…We downgraded the certainty due to high risk of bias. The RCT [21][22][23] were classified as unclear risk of bias (online supplemental table 2). We did not assess publication bias for the success of medical abortion for the RCTs given there are only three studies.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…According to another study, 200 mg mifepristone was administered oral in combination with 800 mcg/ml subcutaneously or transvaginal. Studies on the metabolism of mifepristone concluded that no signifi cant differences in blood concentrations within 48 h of administration with oral doses ranging from 100 to 800 mg without any infl uence to the safety and effi cacy [49][50][51][52].Induced abortions were performed in pregnancies of less than 49, 50-56, 57-63 days or <9 weeks [53][54].…”
Section: Disadvantagesmentioning
confidence: 99%